Decomposability and mental representation of French verbs - Estivalet, Gustavo L.; Meunier, Fanny E. (Frontiers in Human Neuroscience, 2015)
In French, regardless of stem regularity, inflectional verbal suffixes are extremely regular and paradigmatic. Considering the complexity of the French verbal system, we argue that all French verbs are polymorphemic forms that are decomposed during visual recognition independently of their stem regularity. We conducted a behavioural experiment in which we manipulated the surface and cumulative frequencies of verbal inflected forms and asked participants to perform a visual lexical decision task. We tested four types of verbs with respect to their stem variants: a. fully regular (parler ‘to speak’, [parl-]); b. phonological change e/E verbs with orthographic markers (répéter ‘to repeat’, [répét-] and [répèt-]); c. phonological change o/O verbs without orthographic markers (adorer ‘to adore’, [ador-] and [adOr-]); and d. idiosyncratic (boire ‘to drink’, [boi-] and [buv-]). For each type of verb, we contrasted four conditions, forms with high and low surface frequencies and forms with high and low cumulative frequencies. Our results showed a significant cumulative frequency effect for the fully regular and idiosyncratic verbs, indicating that different stems within idiosyncratic verbs (such as [boi-] and [buv-]) have distinct representations in the mental lexicon as different fully regular verbs. For the phonological change verbs, we found a significant cumulative frequency effect only when considering the two forms of the stem together ([répét-] and [répèt-]), suggesting that they share a single abstract and underspecified phonological representation. Our results also revealed a significant surface frequency effect for all types of verbs, which may reflect the recombination of the stem lexical representation with the functional information of the suffixes. Overall, these results indicate that all inflected verbal forms in French are decomposed during visual recognition and that this process could be due to the regularities of the French inflectional verbal suffixes.